2017
DOI: 10.1007/s00348-017-2411-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature decline thermography for laminar–turbulent transition detection in aerodynamics

Abstract: a post-processing method was developed and qualified to determine a quantity proportional to the heat transfer coefficient into the flow. By plotting this quantity for each pixel of the surface, a qualitative, two-dimensional heat transfer map was obtained. The results clearly depicted the areas of onset and end of transition over the full span of the model and agreed with the expected behavior based on the respective flow condition. To validate the approach, surface hotfilm measurements were conducted simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In the subsonic regime, less pronounced temperature differences between the outer flow and the model surface made diagnostics using infrared thermography more difficult. In attempts to improve thermal contrast in the subsonic regime, external [21,22,25,26,[89][90][91] or internal [19,20,24,90] heating elements were often incorporated [82]. With the use of additional heating, both laboratory [19][20][21][22][23][24][25] and in-flight experiments [20,26] have performed successful detection of mean transition using infrared…”
Section: Temperature Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the subsonic regime, less pronounced temperature differences between the outer flow and the model surface made diagnostics using infrared thermography more difficult. In attempts to improve thermal contrast in the subsonic regime, external [21,22,25,26,[89][90][91] or internal [19,20,24,90] heating elements were often incorporated [82]. With the use of additional heating, both laboratory [19][20][21][22][23][24][25] and in-flight experiments [20,26] have performed successful detection of mean transition using infrared…”
Section: Temperature Measurementsmentioning
confidence: 99%
“…This results in relatively large gradients in surface temperature, where the streamwise location of absolute maximum temperature gradient coincides with the mean transition location. This methodology was modified by von Hoesslin et al [25] where the convection-dominant temperature decline of an airfoil subject to a finite heat pulse was recorded. By relating the rate of temperature decline, Λ, to the convective heat transfer coefficient, von Hoesslin et al [25] showed that the transition location could be estimated in the region where the streamwise gradient of Λ was maximized, as Λ was shown to be approximately proportional to the convective heat transfer coefficient.…”
Section: Thermographymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments reported on: (1) the importance of the heating technique, especially when external heating is applied [17], [23], [25], [27], [28]; (2) on the issues selecting the appropriate material for the body [23], [28]- [31], either for the bulk body [28, [29], [31], or by applying a paint or a coating to circumvent the properties of the core at the surface where heat exchanges occur [23], [28]- [30]; (3) and on the choice of a post-processing technique to infer quantitative results.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase differences in temperature between the areas with laminar and turbulent flows, external and/or internal heating of the testing surface is often unavoidable. External heat sources, e.g., halogen lamps [1,2] or recently flash lamps [3] offer high optical power outputs, but need to be positioned close to the measurement object to compensate for high divergence angles of the light cone. This can limit its usability in large industrial wind-tunnel facilities, as the inflow may not be obstructed or altered by the measurement equipment.…”
Section: Introductionmentioning
confidence: 99%